Diet, exercise, and chronic disease [ the biological basis of prevention - Ardies, Curtis Murray (CRC Press, 2014)
"Physical activity and exercise combined with proper nutrition bring therapeutic benefits to individuals diagnosed with chronic disease. This book presents a systems biology approach to exercise and nutritional aspects of chronic disease treatment, management, and prevention. Each chapter presents clinical-based research directly related to each disease along with analysis of the associated cellular, molecular, and biochemical mechanisms. Chapters cover diet, exercise, and weight control as they relate to immune function. Diseases covered include rheumatoid arthritis, diabetes, degenerative disease, atherosclerosis, hypertension, cancer, and osteoporosis"-- Provided by publisher